Milk fever : a novel - Cowan, Lissa M. (Demeter Press, 2013)
In 1789, Armande, a wet nurse who is known for the mystical qualities of her breast milk, goes missing. Céleste, a cunning servant girl who Armande once saved from shame and starvation, sets out to find her. A snuffbox found in the snow, the unexpected arrival of a gentleman and the discovery of the wet nurse's diary, deepen the mystery. Using Armande's diary as a map to her secret past, Céleste fights to save her from those plotting to steal the wisdom of her milk. Milk Fever is a rich and inspired tale set on the eve of the French Revolution--a delicious peek into this age's history. The story explores the fight for women's rights and the rise in clandestine literature laying bare sexuality, the nature of love and the magic of books to transform lives.